Hubungan Pola Asuh Orang Tua Dengan Perkembangan Sosial Remaja Kelas VIII di SMP Negeri 6 Palu - Muhammad Fadhli, Wendi (NHM PRESS, 2024)
Parenting is the way to educate the children and it become parent’s responsibility in constructing of children’s character.The teenager with democratic parenting more confidence than teenager with otoriter parenting, they are inconfidence, agresive and un obedience. The aim of this research to analys the correlation of parenting and social growth of teenager in class VIII of SMP Negeri 6 Palu. This research used cross sectional design and sampling was 170 respondents. The instrument of this research was questionnaire and arrange into form such as demographic data, question about parenting and social growth of teenager. The test used was Fisher’s test. Analyses result shown that among 170 respondents, 169 respondents (96%) have democratic parenting and 7 respondents (4%) have otoriter. But not found permissive parenting in SMP Negeri 6 Palu. Among of 170 respondents, 150 respondents (88%) have good social growth of teenager. Result shown that there is no correlation between parenting with social growth of teenager (P=0,193). For parents could proper obsevation of their children’s attitude, and their peer. For further researcher could do the research about correlation of peer with social growth of teenager except parenting.